2020
DOI: 10.21532/apfjournal.v5i2.155
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Auditor’s Competence and Independence on Information System Audit Quality

Abstract: Users of financial statements always rely on the results of audits conducted by competent andindependent auditors because the audits are carried out through quality processes and efforts. Competent and independent auditors are needed to obtain quality audit results. Because most modern information systems use information technology, the information technology audits become an important component in all external and internal audits. This study aims to examine the effect of auditor’s competence and auditor’s ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…Therefore, hypothesis H3 stated as is accepted by the researcher. This finding is consistent with that of IIA (2014); ; Muluneh (2007); Rusmanto (2012); Salawu (2017); Setiawan et al (2020); Kirima (2016), Shewamene, 2014 and (Tesema, 2018) who found out that professional standards has positive and significant effect on auditor's independence. This indicates existence of professional audit standards has positive influence on independence of auditor's.…”
Section: The Regression Results (Inferential Statistics)supporting
confidence: 88%
“…Therefore, hypothesis H3 stated as is accepted by the researcher. This finding is consistent with that of IIA (2014); ; Muluneh (2007); Rusmanto (2012); Salawu (2017); Setiawan et al (2020); Kirima (2016), Shewamene, 2014 and (Tesema, 2018) who found out that professional standards has positive and significant effect on auditor's independence. This indicates existence of professional audit standards has positive influence on independence of auditor's.…”
Section: The Regression Results (Inferential Statistics)supporting
confidence: 88%
“…This schedules to several possibilities, such as based on the respondent's description, it can be seen that most respondents tend to agree with the auditor's expertise question, meaning that the respondent has sufficient expertise so that it influences performance; as well as auditors, both expert and less skilled, always work under audit standards so that their performance is maintained. The outcomes of this particular examination are actually according to the research study of Setiawan et al, (2020) and Effect et al, (2019) Based upon Dining table 4, it could be viewed that locus of command has a favorable impact on auditor efficiency. The outcomes of this particular examination indicate that auditors who believe that the outcomes acquired are much a lot extra identified through internal and external factors will do their best and will not give up easily, resulting in high efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…Because of their abilities, experts can perform tasks better so that they can perform better and more efficiently. Setiawan et al, (2020) found that expertise has a considerable impact on efficiency. These results are supported by Effect et al, (2019).…”
Section: Introductionmentioning
confidence: 99%